Penerapan Metode Tutor Sebaya dapat Meningkatkan Hasil Belajar Estimasi Biaya Konstruksi pada Siswa Kelas XII Bisnis Konstruksi dan Properti SMK Negeri 2 Karang Baru - Nurhayati (Medan Resource Center, 2022)
This Classroom Action Research (CAR) was carried out considering how important it is to improve the quality of learning outcomes through various ways or optimal learning strategies, where teachers play a very important role in preparing students to take part in learning. The learning method was chosen to improve learning outcomes Estimation of Construction Costs for Class XII Students Design Modeling and Building Information at SMK Negeri 2 Karang Baru Odd Semester TP. 2022/2023. This is considered very necessary because the interest and motivation as well as student learning outcomes in this class are still low. The subjects of this study amounted to 17 people. From the results of the analysis it was found that student learning achievement increased from cycle I first meeting to cycle 2 second meeting namely, cycle I first meeting 60%, cycle I second meeting 65%, cycle II first meeting 80%, cycle II second meeting 95%, classically students achieve mastery of learning outcomes. The conclusion of this study is: Application of the Peer Tutor Method Can Improve Learning Outcomes Estimating Construction Costs in Class XII Students of Design Modeling and Building Information at SMK Negeri 2 Karang Baru Odd Semester TP. 2022/2023, namely Cycle I First Meeting 60%, Cycle I second meeting 65% and Cycle II first meeting 80%, Cycle II second meeting 95% (classical completed).